Muhtawā al-Qirā’ah fi Kitāb Durus al-Lughah al-Arabiyyah li al-Shaff al-Awwal min al-Madrasah al-Tsānawiyyah al-Islāmiyyah li al-Thab’ah 2020 - Muhammad Qadhafi (University of Darussalam Gontor, 2022)
Through this research, the researcher tries to identify the contents of reading skills in Arabic textbook